Educação política: instrumento necessário para melhorar a qualidade da democracia - Lahuerta, Milton [UNESP]; Nascimento, Alessandra Santos [UNESP]; Lopes, Maira Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper aims to contribute to increase the knowledge about political education experiences developed with young people from elementary school through partnerships between the University and the municipal government. To that end, we will present the results of the political education work carried out in 2014 with 1,148 young people from 13 to 16 years old, all students from public and private schools in Araraquara, state of São Paulo. This experience was the product of a partnership made between the Government and Policy Laboratory of FCLAr-UNESP and the City of Araraquara, São Paulo. Besides the training work, the Laboratory has conducted a survey among these young people. This aimed to evaluate the perceptions of these students about institutional policy as well as political education. One of the results of this teaching-learning process was the perception that young people are not so sure about the meaning of democracy, although they value the political participation of citizens in order to change society and agree that political education is necessary. Among some of the new knowledge that these teenagers have acquired we can list the operation of power and elections in Brazil, as well as the role of the citizen.

O presente trabalho visa contribuir para ampliar o conhecimento sobre as experiências de educação política desenvolvidas com jovens do ensino fundamental, através de parcerias entre a universidade e o poder público municipal. Para isso, apresentaremos os resultados do trabalho de formação política realizado em 2014 com 1.148 jovens, de 13 a 16 anos, estudantes das redes pública e privada de ensino de Araraquara. Essa experiência foi produto da parceria entre o Laboratório de Política e Governo/FCLAr-UNESP e a Câmara Municipal de Araraquara/SP. Além da formação, o Laboratório realizou uma pesquisa junto a esses jovens. Esta objetivou aferir as percepções desses estudantes acerca da política institucional bem como da educação política. Um dos resultados desse processo de ensinoaprendizagem foi a percepção de que os jovens não têm clareza sobre o significado de democracia, embora valorizem a participação política dos cidadãos, para a mudança da sociedade, e concordem que a educação política é necessária. Entre os conhecimentos novos que os adolescentes adquiriram encontram-se o funcionamento dos poderes e das eleições no Brasil, bem como o papel do cidadão.
Keywords: Political education; Youth; Democracy; Educação política; Juventude; Democracia